Enhancing Student Morality Through Religious Extracurricular Activities in the COVID-19 Pandemic Era: A Case Study in Elementary Schools in Bogor City - Ginanjar, Muhammad Hidayat; Syukur, Muhamad; Rahman, Rahman; Irvansyah, Irvansyah (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
Purpose – This study examines improving student morality through religious extracurricular activities during the COVID-19 pandemic in Bogor City, West Java elementary schools. Design/methods/approach – Employing a case study method, this research was conducted at SDN Empang 02, Bogor City. Data was collected through participatory observation, in-depth interviews, and document analysis. Data analysis was performed interactively and reflectively to ensure validity through credibility, transferability, dependability, and confirmability criteria. Findings – The findings indicate a significant improvement in students' morality at SDN Empang 02 Bogor during the COVID-19 pandemic. The religious extracurricular program, focusing on developing students' talents and interests, has been effectively planned, organized, implemented, and supervised. Research implications – This study provides new insights into the importance of religious extracurricular activities in shaping student morality, especially in the context of the pandemic. These findings emphasize the need for a comprehensive and integrated approach to education, focusing on academic aspects and developing students' morality and character.